Pengaruh DER Terhadap ROA pada Perusahaan Sektor Pertanian Terdaftar Bursa Efek Indonesia - Vira Septi Ayu Hasanah; Fatmi Hadiani; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This final project entitled Effect of DER on ROA in Agricultural Sector Companies on Indonesia Stock Exchange 2010-2019. The purpose is to determine the development of DER and ROA as well as to determine the effect of DER on ROA. The method writer used is a quantitative approach with panel data regression model as analytical tool, and Eviews 10 as statistical tools. The result using t-test is accepting hypothesis, meaning that DER does not have a positive and significant effect on ROA.